THE EFFECT OF INTRAPERSONAL INTELLIGENCE STRATEGY TO IMPROVE STUDENTS' WRITING DESCRIPTIVE PARAGRAPHS IN THE SECOND GRADE OF SMAN 2 KUPANG - Nahak, Anggelina Martina; Hoinbala, Festif Rudolf; Marpaung, Tiarma (Journal of Language, Education, Literature, and Culture, 2023)
The main objective of this study was to determine the effect of the Intrapersonal Intelligence strategy in improving students' writing descriptive paragraphs. This study was conducted at SMAN 2 Kupang. The population was 63 students of grade eleven. The method used in this study was a quantitative method using a quasi-experimental design. The instrument was a written test, and the t-test formula was used in the data analysis. The results of this study indicated a significant difference between the experimental group and the control group, with the mean score in the experimental group being 70.6 and the mean score in the control group being 50.6. Whereas in the paired test samples, there were significant results between the pre-test and post-test based on the result of the value, the value of the t-test (15.8) was higher than the value of t-table (2.058) with df = N-2. This showed that the effect of the intrapersonal intelligence strategy can improve students' skills in writing descriptive paragraphs. As the intrapersonal intelligence strategy can develop students' thinking to be broader and more dynamic, it can be used as an alternative teaching strategy in improving students' descriptive paragraph writing. Keywords: intrapersonal intelligence strategy, writing, descriptive paragraph